Analysis of social support for households with children in Kazakhstan - Temirbayeva, D.M. (BUKETOV BUSINESS REVIEW, 2019)
The article analyzes social payments to households with children in Kazakhstan. The article presents a comprehensive model of support for families with children, which includes a system of state benefits, social benefits, as well as measures to promote employment in the country and tax benefits. The main directions of social support to families of mothers with children under one year, children with disabilities are revealed. The assessment of state targeted assistance to low-income families and large families, as well as to families that have lost a breadwinner and have taken children under guardianship or guardianship is carried out. The analysis revealed that the well-being of households or individuals is determined by the per capita current cash income of the population, which is used to determine the level of poverty, inequality, dynamics of living conditions of the population. A comparative analysis of the amount of social benefits per year in the country and the system of periodic social benefits for the child in a number of countries has been carried out. The solution of problems of households with children depends on the developed tactics and strategy of the state in the field of social policy. The well-being of households with children depends to a large extent on the state's social policy and state programmes.